2016
DOI: 10.3747/co.23.2873
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic Chemotherapy and Radiotherapy as Salvage Treatment in Refractory or Relapsed Pediatric Solid Tumours

Abstract: Background Metronomic chemotherapy (mctx) combined with radiation therapy (rt) is an emerging anticancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Although metronomic chemotherapy is regarded as an innovative multitargeted therapy 6,7 and is being promoted as an attractive option for low-and middle-income countries, 8,9 limited phase 1 and 2 data exist. In most of the published literature on pediatric metronomic chemotherapy, studies 9,[11][12][13][14][15][16][17] have found benefit in terms of disease stabilization and have recorded it as clinical benefit. We do not actually have randomized comparative data to indicate that indeed this stabilization of disease is attributable to action of metronomic chemotherapy and not merely because of the natural history of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although metronomic chemotherapy is regarded as an innovative multitargeted therapy 6,7 and is being promoted as an attractive option for low-and middle-income countries, 8,9 limited phase 1 and 2 data exist. In most of the published literature on pediatric metronomic chemotherapy, studies 9,[11][12][13][14][15][16][17] have found benefit in terms of disease stabilization and have recorded it as clinical benefit. We do not actually have randomized comparative data to indicate that indeed this stabilization of disease is attributable to action of metronomic chemotherapy and not merely because of the natural history of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is also noted that in some studies, addition of radiotherapy may have contributed substantially to the good response rather than metronomic chemotherapy itself …”
Section: Clinical Usage In Pediatricsmentioning
confidence: 99%
“…The first RCT in the palliative setting and retrospective analysis of medulloblastomas with the COMBAT regimen have been reported from India . Ali and El‐Sayed published the clinical experience of metronomic combinations in relapsed pediatric malignancies in Egyptian children . Potential use of metronomic therapy in pediatric acute myeloid leukemia and Ewing sarcoma, along with rural outreach programs based on metronomics, have also been developed in India .…”
Section: Enthusiasm In Low‐ and Middle‐income Countries: Pharmaco‐ecomentioning
confidence: 99%
See 1 more Smart Citation
“…phamide, and methotrexate) and one intravenous drug (vinblastine) in children with relapsed or progressing extracranial tumors. The choice of a MC in our pediatric population stands on previous studies in pediatrics [6][7][8]15,[21][22][23][24][25]. Zapletalova et al6 reported good results with the COMBAT regimen based on a combination of temozolomide, etoposide, celecoxib, vitamin D, fenofibrate, and retinoid acid.…”
mentioning
confidence: 99%